Queer Saint : the cultured life of Peter Watson, who shook twentieth-century art and shocked high society. - Clarck, Adrian; Dronfield, Jeremy (London : John Blake Publishing, 2015)
Fonds Suzan Daniel (FSD)
Engels
Monografie